Effects of Korean Traditional Medicine Treatment on Spontaneous Osteonecrosis of the Knee: A Case Report - Soo-Kyung Lee; Eun-Young Park; June-Haeng Lee; Sun-Woo Kang; Yoon-Jae Won; Myeong-Yeol Yang; Jae-Joon Ha (MEDrang Inc., 2022)
Spontaneous osteonecrosis of the knee (SONK) is a common form of osteonecrosis of the knee and mainly affects the medial condyle due to localized vascular insufficiency. We report a case of SONK in a 65-year-old woman who had severe knee pain in her left knee whichimpeded her capacityto walk beyond 10 minutes. Bilateral knee X-rays revealed degenerative osteoarthritis of both knees and magnetic resonance imaging revealed R/O SONK in the lateral aspect of the medial femoral condyle, as well as a medial meniscal posterior horn root tear, and a Grade 1 medial collateral ligament injury. She was hospitalized at Jaseng Hospital of Korean Medicine for 21 days and receivedcombination therapy includingacupuncture, pharmacopuncture, and herbal medicine. Patient-reported scales indicated that her pain and physical functional limitations were alleviated. Combination therapy consisting of Korean traditional medicine may bean alternative non-operative treatment approach for patients with SONK.